Assessing short evolution brucellosis in a highly brucella endemic cattle keeping population of Western Uganda: a complementary use of Rose Bengal test and IgM rapid diagnostic test - Arnold Ezama; Jean-Paul Gonzalez; Samuel Majalija; Francis Bajunirwe (BMC, 2018)
Abstract Background Brucellosis is a worldwide and zoonotic disease often sadly misdiagnosed in endemic areas. Challenges of availability and accessibility of diagnostic tools are common in resource constrained populations where the most vulnerable are found, surveillance and diagnosis are limited too. Methods A cross-sectional study using a simple two stage cluster sampling method was conducted to measure short evolution brucellosis burden among cattle keeping households that are one of the highest risk populations to be exposed to Brucella infection. A total of 216 households were randomly selected from 18 rural villages from the Western Region of Uganda. Household blood samples were tested for Brucella antibodies using the highly sensitive Rose Bengal test (RBT) and IgM ELISA Lateral Flow Assay (LFA). Results Among the total tested population, 58.8% did not react with any of the tests, 13.4% reacted with both tests. Among those that reacted with both (N = 29), 62.1% had weak (+ 1) LFA staining, 34.5% had moderate (2+) LFA staining. Altogether, both weak and moderate staining (96.5%) are consistent with sub-acute disease, while only one (3.4%) had strong (3+) LFA staining consistent with acute infection. 19.4% of the samples tested positive only with RBT, consistent with chronic infection, eighteen samples (8.3%) reacted exclusively with IgM LFA. Conclusion We identified a high prevalence of short evolution brucellosis in the cattle keeping household members. Prevalence of chronic infection diagnosed with RBT only was higher than the prevalence of short evolution brucellosis. IgM LFA results depict possible cases of cross reaction with Salmonella spp., Plasmodium etc. Ultimately, we identified a consistent prevalence of short evolution brucellosis in the cattle keeping household members. Indeed, the use of a combined diagnostic with LFA and RBT is easy and amenable for an active disease surveillance and accurate diagnosis in rural settings.